Fundamental models and management principles regional market of tourism (Путеводитель предпринимателя)
The article considers the process of interaction between different sectors of the economy, representing the basic model for the perspective development of tourism. In this case, to increase the efficiency of mutually beneficial cooperation and development of tourism it is necessary to consolidate the efforts of public authorities and representatives of tourist business.